Technology Adoption for Active and Healthy Ageing among Current and Future Generations of Older Adults - Offerman, Jens (Lund University, Faculty of Medicine Doctoral Dissertation Series, 2025)
To promote active and healthy ageing (AHA), it is essential to understand how different generations engage with digital technologies, as these tools are becoming increasingly integral to everyday life. This thesis project explored technology adoption among men and women from three age groups representing different generations (30–39, 50–59 and 70–79 years), focusing on attitudes, usage patterns, and factors that facilitate or hinder engagement with technologies intended to support AHA. Using a multi-methods approach, four interrelated studies were conducted. The first study, based on a national survey, examined generational attitudes toward a broad spectrum of technologies and their relevance in supporting AHA. Using the same dataset, the second study investigated how socio-demographic factors and attitudes towards digital technology were associated with reported ability to keep up with technological developments. Based on data from a national panel, the third study captured self-reported changes in digital technology use and attitudes during the early phase of the COVID-19 pandemic, providing insights into how period effects might influence digital engagement. The fourth study employed focus group interviews in an experimental housing environment to explore perceived barriers and facilitators to adopting smart home technologies among current and future older adults. The generational perspective reveals that shared or overlapping views on technology can be more influential than age-based stereotypes when it comes to technology attitudes and adoption. Rather than labelling older adults as inherently “technophobic”, or younger adults as automatically “tech-savvy,” the findings show that attitudes toward technology are more strongly influenced by perceived usefulness, personal motivation, and prior experience than by age alone. Generational labels, while useful for capturing differences in digital familiarity and exposure, do not fully account for variation in adoption. Instead, technology engagement is shaped by individual resources, social influence, structural support, and sustainability concerns. Overall, this thesis contributes to a more nuanced understanding of technology adoption that moves beyond chronological age. Challenging prevailing assumptions about ageing and technology, the findings underscore the need for inclusive and sustainable technology design, lifelong digital support systems, and policy attention paid to structural barriers such as affordability and access. These efforts are important to ensure that digital technologies can support autonomy, participation, and well-being for both current and future generations of older adults.
Keywords: Teknikanvändning; Ålderism; digitalt utanförskap; aktivt och hälsosamt åldrande; digital inkludering; Technology adoption; active and healthy ageing; digital inclusion; digital divide; ageism